Therapeutic bullfrog oil-based nanoemulsion for oral application: Development, characterization and stability - Rutckeviski Renata; Xavier Francisco Humberto; Morais Andreza Rochelle Do Vale; Amaral-Machado Lucas; Alencar Everton Do Nascimento; Genre Julieta; De Souza Araujo Adriano Antunes; Egito Eryvaldo Socrates Tabosa Do (Acta Pharmaceutica)
The aim of this study was to develop, optimize, and characterize a stable therapeutic bullfrog oil based nanoemulsion for oral application using a rational experimental design approach. The optimized oral nanoemulsion contained 0.2 % sodium benzoate and 0.02 % propyl-paraben as preservatives; 0.1 % sucralose and 0.4 % acesulfam K as sweeteners and 0.1 % tutti-frutti as flavoring to mask the unpleasant organoleptic characteristics of bullfrog oil. The oral O/W-nanoemulsion showed the droplet size, PDI, zeta potential, and pH of 410 ± 8 nm, 0.20 ± 0.02, –38 ± 2.5 mV, and 6.43 ± 0.05, respectively. The optimized oral nanoemulsion showed a milky single-phase and optimal physical stability at 25 °C for 90 days. Indeed, higher oxidation induction time and lower formation of peroxides in the oral nanoemulsion were responsible for improving its stability. A therapeutic delivery system containing bullfrog oil for oral application was successfully developed and optimized with ideal thermo-oxidative stability.